Mapping RNA–RNA interactome and RNA structure in vivo by MARIO - Tri C. Nguyen (Nature Portfolio, 2016)
Current methods for mapping RNA-RNA interactions have to rely on an ‘anchor’ protein or RNA. Here, the authors report the MARIO (Mapping RNA interactome in vivo) technology that can massively reveal RNA-RNA interactions and RNA structure from unperturbed cells.